Nghiên cứu sự tạo vòng furoxan từ nhánh allyl của axit eugenoxyaxetic - Đĩnh, Nguyễn Hữu; Tuyết Lan, Hoàng Thị; Hoan, Phạm Văn; Hiển, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
Eight furoxans were synthesized starting from eugenoxyacetic acid by isomerization following with cyclization, hy®razidation and nitration. The structure of the furoxans has been examined by IR, LC-UV, 1H NMR, 13C NMR and MS spectroscopy.